Liver Targeting of Daclatasvir via Tailoring Sterically Stabilized Bilosomes: Fabrication, Comparative In Vitro/In Vivo Appraisal and Biodistribution Studies - El-Nabarawi M (Dove Medical Press, 2021)
Mohamed El-Nabarawi,1 Mohamed Nafady,2 Shahira Elmenshawe,3 Marwa Elkarmalawy,4 Mahmoud Teaima1 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 2Department of Pharmaceutics and Clinical Pharmacy, Faculty of Pharmacy, Nahda University, Beni-Suef, Egypt; 3Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Beni-Suef University, Beni-Suef, Egypt; 4Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Modern University of Technology and Information, Cairo, EgyptCorrespondence: Shahira Elmenshawe Email Shahira.elmenshawe@yahoo.comIntroduction: Hepatitis C virus (HCV) is a significant public health concern that threatens millions of individuals worldwide. Daclatasvir (DAC) is a promising direct-acting antiviral approved for treating HCV infection around the world. The goal of this study was to encapsulate DAC into novel polyethylene glycol (PEG) decorated bilosomes (PEG-BILS) to achieve enhanced drug delivery to the liver.Methods: DAC-loaded BILS were primed by a thin film hydrating technique. The study of the impact of various formulation variables on the properties of BILS and selection of the optimal formulation was generated using Design-Expert® software. The optimum preparation was then pegylated via the incorporation of PEG-6-stearate (5% w/w, with respect to the lipid phase).Results: The optimum PEG-BILS formulation, containing PL:SDC ratio (5:1), 5 mg cholesterol, and 30 min sonication, yielded spherical vesicles in the nanoscale (200± 15.2 nm), elevated percent of entrapment efficiency (95.5± 7.77%), and a sustained release profile of DAC with 35.11± 2.3% release. In vivo and drug distribution studies revealed an enhanced hepatocellular delivery of DAC-loaded PEG-BILS compared to DAC-unPEG-BILS and DAC suspension, where DAC-PEG-BILS achieved 1.19- and 1.54 times the AUC0– 24 of DAC-unPEG-BILS and DAC suspension, respectively. Compared with DAC-unPEG-BILS and DAC suspension, DAC-PEG-BILS delivered about 2 and 3 times higher DAC into the liver, respectively.Conclusion: The innovative encapsulation of DAC-PEG-BILS has a great potential for liver targeting.Keywords: antiviral drug, nanodrug delivery system, bile-based nanovesicles, Box–Behnken approach, liver targeting parameters, pharmacokinetic, bioavailability